Pioneering terahertz blood analysis: Hollow-core PCF with optimized sensitivity and low loss. - A H M Iftekharul Ferdous; Md Shahadat Hosen; Kayab Khandakar; Diponkar Kundu; Most Momtahina Bani; Khalid Sifulla Noor; Suchana Aktar Tithi (PLoS ONE)
Blood detection is crucial for the human body. Its detection is very crucial and sensitive. In this paper, a hollow core photonic crystal fiber (PCF) biosensor operating in the terahertz frequency range is proposed. The building blocks of this proposed biosensor's hexagonal cladding structure are the same square-shaped air gaps in the cladding and core. Hemoglobin, white blood cells (WBC), red blood cells (RBC), plasma and water are among the analytes that fill the core. The sensing aspects of the design will be examined using the finite element method. The COMSOL v6.1a software simulation findings show that the sensitivity for water is 93.08 percent, for plasma it is 94.55%, for hemoglobin it is 96.21%, for WBC it is 95.16%, and for RBC it is 97.05 percent. The suggested design's detection has the lowest confinement loss at frequencies between f =  1 and 2.8 THz. In addition to these, the design exhibits, under ideal design circumstances, very low and flattened dispersion, huge beam divergence, improved effective area, substantial birefringence, and negligible effective material loss. This proposed PCF biosensor is a viable option for employment in various practical applications due to its simple shape and great detecting capacity. PCF offer significant benefits for blood component analysis due to their unique structure and light-guiding properties. By enabling precise control over light-matter interaction, PCFs can be highly sensitive to the presence and characteristics of different blood components, such as red and white blood cells, platelets, hemoglobin, and glucose. This has major implications in medical diagnostics, offering advantages in speed, sensitivity, and minimally invasive testing.